Conventional and islamic business coaching: impact on small business performance in Indonesia - Muhammad Sholahuddin (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2020)
In the last decade, many small-scale Muslim entrepreneurs in Indonesia incorporated sharia guidance into their business practices. Although business coaching is recognised to contribute to a successful business, no empirical evidence has been reported between the conventional and sharia business coaching and its implications on business performance in Indonesia. This study aims to investigate four objectives. They are to determine the characteristics of conventional and Islamic business coaching, to analyse and compare the impacts of conventional and Islamic business coaching on the performance of small businesses in Indonesia and to provide suggestions and recommendations regarding the practice of IBC to increase their impacts on the performance of small businesses. Prior to initiating the assessment of the objectives, we interviewed 10 Islamic business coaches to determine the characteristics of Islamic business coaching which exists in several constructs. The responses were then used to refine the questionnaire implemented during the pilot project. The questionnaires were distributed to 300 respondents who have engaged in conventional and Islamic coaching (150 respondents each). The quantitative analysis was performed using structural equation modelling (SEM). Based on the analysis, the characteristics of the conventional business coaching included the role of a business coach, subjects focused during business coaching sessions, results, satisfaction and self-efficacy variables. Meanwhile, the characteristics of Islamic business coaching was similar to that of the conventional coaching with additional Islamic values namely business coaching (Islamic) value, spirituality and business ethics in both session and result variables. All of the variables were identified to hold significantly positive effects on the small business performances comprising of financial, organisational and strategic performances. Moreover, these variables demonstrated high positive impacts on Islamic business coaching compared to conventional coaching based on the performance of small businesses. The results from this research have provided more insight to academicians and practitioners on the definition of conventional and Islamic business coaching, its application and its impact on the performances of small businesses in Indonesia. Hence, we recommend small businesses in Indonesia to strengthen the foundation of Islamic value and spirituality by incorporating Islamic business coaching to improve their business performance. Keywords: Islamic business coaching, value, ethics, session focus, performance